The Eigenfunction Expansion for a Dirichlet Problem with Explosive Factor - Zaki F. A. El-Raheem; A. H. Nasser (Abstract and Applied Analysis)
We prove the eigenfunction expansion formula for a Dirichlet problem with explosive factor by two ways, first by standard method and second by proving a convergence in some metric space 𝐿2(0,𝜋;𝜌(𝑥)).